An Action-Based Model of Cognitive-Dissonance Processes. (June 2015) - Harmon-Jones, Eddie; Harmon-Jones, Cindy; Levy, Nicholas
The action-based model extends the original theory of cognitive dissonance by proposing why cognitive inconsistency causes both dissonance and dissonance reduction. The model begins by assuming that many perceptions and cognitions automatically impel us to act in specific ways. It then posits that the negative affective state of dissonance is aroused not by all cognitive conflict but, specifically, when cognitions with action implications are in conflict with each other, making it difficult to act. The dissonance signals to the organism that there is a problem and that the cognitive inconsistency needs to be resolved so that behavior can occur. After presenting the action-based model, we review results from behavioral and neuroscience experiments that have tested predictions derived from it.